2018
DOI: 10.1111/btp.12551
|View full text |Cite
|
Sign up to set email alerts
|

Bird mixed‐species flock formation is driven by low temperatures between and within seasons in a Subtropical Andean‐foothill forest

Abstract: According to both the predation avoidance and foraging efficiency hypotheses, birds within mixed flocks increase their foraging efficiency and/or can spend more time feeding and less time looking out for predators. These hypotheses predict that birds in mixed flocks obtain benefits. Thus, mixed flock formation could serve as a strategy to cope with difficult conditions imposed on birds such as climatic conditions that ultimately result in a change in predation pressure or food resources. We evaluate the hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Under such a scenario, the immigration of species with similar or new sets of functional traits could compensate for the loss of other species 4,54,55 . However, upward movements does not only depend on climate, but also on interactions among birds, such as interspecific competition 56 or foraging interactions in mixed species flocks 57 . While knowledge on biotic factors shaping species’ distributions is available for some species, comprehensive information is currently lacking for species-rich tropical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Under such a scenario, the immigration of species with similar or new sets of functional traits could compensate for the loss of other species 4,54,55 . However, upward movements does not only depend on climate, but also on interactions among birds, such as interspecific competition 56 or foraging interactions in mixed species flocks 57 . While knowledge on biotic factors shaping species’ distributions is available for some species, comprehensive information is currently lacking for species-rich tropical systems.…”
Section: Discussionmentioning
confidence: 99%
“…Among the few studies that have attempted to tease apart the nature of these adaptations, most results indicate a shift in community structures in response to changes in resource availability (e.g. [27][28][29][30]).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to keep in mind that the results from this study and [ 24 ] are based on the four primary species found in mixed-species flocks in north temperate forests (see [ 9 , 31 , 76 ]. The behavioral responses to habitat degradation observed in these flocks may differ from that found in tropical forests (e.g., [ 77 ], where seasonal variation in food availability and energetic stress is typically less than in temperate climates [ 78 ]. Moreover, the patterns we describe here may result from an increased importance of species-specific associations where species diversity is quite low [ 23 ].…”
Section: Discussionmentioning
confidence: 99%